Various Methods of Strengthening Reinforced Concrete Beam-Column Joint Subjected Earthquake-Type Loading Using Fibre-Reinforced Polymers: A Critical Review - Ridwan, Ridwan; Jemaa, Yaser; Yuniarto, Enno (Faculty of Engineering Universitas Riau and Applied Materials and Technology Society, 2023)
Fibre-reinforced polymer (FRP) composites are extensively employed in concrete technology due to their exceptional mechanical strength and durability. They serve a dual purpose, not only reinforcing damaged elements but also supporting heavier service loads and addressing long-term concerns in new infrastructure projects. Consequently, the objective of this review is to establish a comprehensive research database that focuses on evaluating the strengthening behaviour of reinforced concrete (RC) beam-column joints (BCJ) under earthquake loads through diverse types and application methods of FRP composites. The efficacy of these strengthening techniques is assessed by considering factors such as the loading capacity and dissipated energy of RC BCJ versus the joint confinement index provided by the fibre in the joint area. Through this state-of-the-art review, it becomes evident that FRP composites effectively enhanced the normalized load of specimens up to 27 kN/?MPa and enhanced the dissipated energy until 558.6 kN-mm for the case of specimens with a lower confinement index, less than 0.3. Additionally, the specimen strengthened with the deep embedment (DE) method resulted in a moderate normalized load and dissipated energy compared to those strengthened with the external bonded (EB) method. The test results indicated that the average normalized load and dissipated energy of the DE-strengthening method was 93% and 28.5% compared to that of the EB-strengthening method. These findings reveal that FRP composites offer distinct advantages in terms of load capacity and dissipated energy when used for strengthening earthquake-affected RC BCJ. Finally, based on the compilation of the previous works, this research proposes several techniques for utilizing FRP composites to enhance RC BCJ subjected to earthquake load.